2020
DOI: 10.1016/j.artd.2020.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Excellent midterm survival and functional outcomes of a fully hydroxyapatite-coated cementless stem: first results of a prospective multicenter study

Abstract: Background: The Polarstem (Smith & Nephew, Baar, Switzerland) is a tapered straight stem, an implant with an excellent survival rate. Although the most recent annual report of the National Joint Registry in the United Kingdom also reports excellent survivorship for the cementless Polarstem, no prospective studies have been published focusing on both its efficacy and clinical performance. Therefore, the present study was designed to prospectively evaluate its functional and radiographic outcomes at midterm. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…The long-term revision rate of the POLARSTEM is lower than that of other cementless stems, and the results have been reported to be good [5]. Good midterm results at 7 y postoperatively and long-term results at 11 y postoperatively have also been reported [27][28][29]. The SBF observed using DTS in the present study may reflect the effect of the HA coating and may contribute to the good long-term results of the POLARSTEM.…”
Section: Discussionsupporting
confidence: 55%
“…The long-term revision rate of the POLARSTEM is lower than that of other cementless stems, and the results have been reported to be good [5]. Good midterm results at 7 y postoperatively and long-term results at 11 y postoperatively have also been reported [27][28][29]. The SBF observed using DTS in the present study may reflect the effect of the HA coating and may contribute to the good long-term results of the POLARSTEM.…”
Section: Discussionsupporting
confidence: 55%
“…Many studies have reported on outcomes of HA-coated stems [1,8,9,28,29], but only a few have reported on outcomes of other coatings. Studies on stems with first plasma-sprayed titanium and then HA coating have reported satisfactory mid-and long-term outcomes [6,[30][31][32], this coating combination may provide stronger biological and mechanical bone fixation compared to only HA coating [6,33,34]. A recent study by Liu et al [35] has shown that a pore size between 50 and 800 μm stimulates bone ingrowth.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the first porous Ti coating, together with the external layer of HA, showed a synergic combination promoting fast implant osseointegration and stronger mechanical fixation with bone [ 29 ]. Some recent studies have reported excellent mid- to long-term stem survivals with the Polarstem, a Corail-design plasma-sprayed stem with 180 μm porous Ti and 50 μm HA, suggesting that this type of double Ti/HA plasma-sprayed coating could massively reduce the risk of implant aseptic loosening [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%